Experimental and numerical analysis to predict the performance of a turboexpander at cryogenic temperature - Kumar M.; Biswal R.; Behera S.K.; Kumar A.; Sahoo R.K. (My University, 2025)
The emerging trend for using cryogenic fluids in scientific and research applications requires a Claude cycle-based efficient turboexpander system. This paper presents the mean-line design procedure, numerical, and experimental investigation to distinguish the fluid flow and thermodynamic analysis of a turboexpander operating at cryogenic temperature. Initially, the mean-line design of turboexpander components has been carried out. Thereafter, the three-dimensional model and computational mesh of nozzle, turbine, and diffuser have been generated using ANSYS BladeGen® and ICEM®. The three-dimensional computational fluid dynamics analysis has been carried out to characterize the effect of fluid flow properties such as pressure, velocity, and thermal properties such as temperature, static enthalpy, and entropy at different axial locations. Finally, an experimental test rig has been developed to examine the performance of the turboexpander at cryogenic temperature and validating the numerical findings for a case study. The methodology provides insight into the realistic fluid flow phenomenon and thermal performance of a turboexpander under rotating conditions, as it is the most essential and expensive part of a gas liquefaction system. © 2020 The Authors. Engineering Reports published by John Wiley & Sons, Ltd.